Analisis Aktivitas Siswa Menggunakan Model Direct Instruction dengan Metode Mind Mapping - Muhammad Arifuddin; Julian Yudani; Misbah Misbah; Dewi Dewantara (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The application of models and methods that are not in accordance with the characteristics of teaching materials has an impact on the low activity of students. Therefore, this research was conducted with the aim of analyzing student activities after applying the direct instruction model with the mind mapping method. This research is a classroom action research with Hopkins design. This study consisted of two cycles with two meetings per cycle. The subjects of this study were students of class XI IPA SMAN 11 Banjarmasin. Data collection techniques were obtained through observation. The results showed that student activity increased from 68.12% to 75.38% in the active category. It was concluded that the direct instruction model with the mind mapping method could increase the activity of class XI science students at SMAN 11 Banjarmasin.